1994
DOI: 10.20506/rst.13.3.808
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of contagious ecthyma in camels (Camelus dromedarius) in the Turkana district of Kenya

Abstract: Gitao, C G Date: 1994 Mortality among camel calves (Camelus dromedarius) is one of the most serious problems faced by camel herdsmen and, although there are several reasons for this mortality, diseases play a major role. In an investigation of outbreaks of contagious ecthyma in camels in the Turkana district of Kenya, four outbreaks were detected involving only camel calves. The principal lesions were distinct or largely coalesced pustules on the mouth, nose and muzzle. Direct electron microscopy of infected s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Analogous lesions caused by parapoxvirus were also observed in camels (Gitao, 1994) and in a red deer (Scagliarini et al, 2011). Skin nodules located in head, neck and thorax, were reported in a sea lynx (Zalophus californianus) infected with parapoxvirus (Nollens et al, 2006).…”
Section: Figure 10: Ultrathin Section Of the Crusts Fragments Observmentioning
confidence: 72%
See 1 more Smart Citation
“…Analogous lesions caused by parapoxvirus were also observed in camels (Gitao, 1994) and in a red deer (Scagliarini et al, 2011). Skin nodules located in head, neck and thorax, were reported in a sea lynx (Zalophus californianus) infected with parapoxvirus (Nollens et al, 2006).…”
Section: Figure 10: Ultrathin Section Of the Crusts Fragments Observmentioning
confidence: 72%
“…Through this technique, parapoxvirus can easily be differentiated from orthopoxvirus by its different morphologies, with electron microscopy being one of the techniques chosen by the OIE to diagnose contagious ecthyma (Gitao, 1994;OIE, 2007).…”
Section: Figure 10: Ultrathin Section Of the Crusts Fragments Observmentioning
confidence: 99%
“…In an earlier study, clinical feature observed was the appearance of pustules on the nose, muzzle and lips and the enlargement of the lymph nodes [20]. Moallin et al [21] recorded only localized lesions on the muzzle and lips.…”
Section: Discussionmentioning
confidence: 95%
“…However, in another study in Saudi Arabia [25], camels were not observed to be cross-infected under field conditions, although they were in close proximity with sheep and goats. Gitao [20] reported that the common practice of keeping all camel calves in the same shelter at night could be responsible for the spread of the virus by contact, and he also proved that the outbreak in camel calves occurred when Parapoxvirus infections were also observed in goat kids who were raised in closed proximity place [17,20]. In the reported causes of the disease in camels, sheep and goats were proven to be carriers and non-carriers of contagious ecthyma.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially fatal parasitic diseases of camels (trypanosomiasis, tick paralysis) (Musca and Osman 1990; Manefield and Tinson 1997;Agab 2006) and potentially fatal viral diseases of camels (camel pox, parapox (contagious ecthyma), Rift Valley fever) (Jezek et al 1983;Gitao 1994;Pfeffer et al 1998;ProMED 2006;Bardsley 2007) have been extensively reported in Africa (Sudan, Ethiopia, Eritrea, Somalia, Kenya) and the Arabian Gulf (United Arab Emirates, Saudi Arabia), but are still exotic to Australian camels. A survey on a Saudi Arabian camel dairy farm indicated that more than 50% of deaths were attributed to trypanosomiasis, with diazinon poisoning being the second most common cause of death (15% of causes) (Agab 2006).…”
Section: Bacterial Viral and Parasitic Risksmentioning
confidence: 99%